Postoperative visual loss in orthopedic spine surgery in the prone position: A case report - Pathomporn Pin-On (2018)
© 2015, Medical Association of Thailand. All rights reserved. Postoperative visual loss is rare but a devastating postoperative complication. It is a multifactorial etiology. The practice advisory for perioperative visual loss associated with spine surgery reported by the American Society of Anesthesiologists task force on perioperative visual loss was developed from several case reports and case series. We reported a new case of postoperative visual loss diagnosed as ischemic optic neuropathy after undergoing a spine surgery in prone position. This case should be added to the overall incidence of postoperative visual loss. The possible risk factors were categorized in order to identify the POVL-susceptible patients. The pathophysiology of ischemic optic neuropathy was briefly reviewed.